(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
The cutting design of the chain saw is defined by the number, the arrangement and the geometry of the cutting tools. When using chisel cutting tools, the cross sectional area of the cut and the shape of the groove are determined by the width and depth of the cut. The laboratory tests analyzed the impact of the cross sectional area and the shape of the cut on the forces and the specific energy. The testing was performed on a linear cutting machine with tool holders and cutting tools in real-scale size. According to the processed statistical data, increasing the cross sectional area of the cut reduces the specific energy, whereby the width of the cut has a considerably larger impact. The tests have shown that besides the cross sectional area of cut, the shape of the surface also affects the forces and specific energy. Through increasing the width to depth ratio upon a constant cross sectional area of the cut, the value of the specific energy and the cutting forces are reduced. Above the width to depth ratio of 2.5 the cutting forces and the specific energy appear to be constant.